New species of Plesionika Bate, 1888 (Crustacea, Decapoda, Pandalidae) from Southwestern Atlantic - Cardoso, Irene A. (Zootaxa, 2011)
The pandalid genus Plesionika Bate, 1888 includes 92 species and has a widespread distribution. The new Plesionika species described herein was sampled by the oceanographic program REVIZEE Central (Fishery) at the Central Brazilian coast (from 11 o S to 22 o S) in depths ranging from 200 to 2000 m using ARROW and GOV nets. Additional material of the new species from the collection of Universidade Federal do Rio Grande (FURG), sampled at South Brazilian coast was also examined. Plesionika revizeei n. sp. is closely related to P. willisi (Pequegnat 1970), and the main feature that distinguishes these two species is the presence of epipods on pereopods 1–4 in the new species. This study provides a full description of the new species and an identification key to the Southwestern Atlantic species of Plesionika.